Penyuluhan Teams Games Tournament (TGT) Terhadap Meningkatnya Pengetahuan Gizi Seimbang Pada Remaja - Niswatul Hurri; Inyoman Adiyasa; Yuli Laraeni (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Adolescence is very important because it is a transitional period between children and adults.Balanced nutrition at this time will greatly determine their maturity in the future, the imbalance between food and needs in adolescents will cause nutritional problems, one of which is malnutrition. Nutrition counseling with the Teams Games Tournament (TGT) method is an easy-to-implement extension method, and involves all individuals without having to have status differences, involving the role of children as peer tutors, containing elements of play and appreciation. PurposeTo find out the effect of counseling with the Teams Games Tournament (TGT) Method on Balanced Nutrition Knowledge in Adolescents at Aikmel Middle School 2 East Lombok Regency. MethodThis research is a pre-experiment research with a design design for one group pre-test and post-test.. Samples were taken by simple random sampling. The results of the knowledge using the Paired Samples Test test obtained the value of p value = .000 or p <α = 0.05, so that there was an influence of counseling with the Tams Games Tornament (TGT) method on Balanced Nutrition in Teenagers at Aikmel Junior High School 2.The Conclusionisthe results showed that there was an increase in the knowledge of adolescents before and after being given balanced nutrition counseling with the Teams Games Tournament (TGT) Method and there was a significant effect on the knowledge of adolescents before and after counseling with the Teams Games Tournament (TGT) method.